2008
DOI: 10.1063/1.2924120
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of semifluorinated alkane diblock copolymers

Abstract: The liquid-vapor interfacial properties of semifluorinated linear alkane diblock copolymers of the form F(3)C(CF(2))(n-1)(CH(2))(m-1)CH(3) are studied by fully atomistic molecular dynamics simulations. The chemical composition and the conformation of the molecules at the interface are identified and correlated with the interfacial energies. A modified form of the Optimized Parameter for Liquid Simulation All-Atom (OPLS-AA) force field of Jorgensen and co-workers [J. Am. Chem. Soc. 106, 6638 (1984); 118, 11225 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 55 publications
7
46
0
Order By: Relevance
“…Liquid densities were also calculated for F5H5 and found to be in excellent agreement with the simulations of Pierce et al 56 The results are presented in Table 6 and plotted in Figure 8, from which a number of conclusions can be drawn. As can be seen from the figure, the simulations are able to predict the liquid densities in excellent agreement with the experimental results.…”
Section: Molsupporting
confidence: 63%
“…Liquid densities were also calculated for F5H5 and found to be in excellent agreement with the simulations of Pierce et al 56 The results are presented in Table 6 and plotted in Figure 8, from which a number of conclusions can be drawn. As can be seen from the figure, the simulations are able to predict the liquid densities in excellent agreement with the experimental results.…”
Section: Molsupporting
confidence: 63%
“…Pierce et al [18] used two different force fields to study the interfacial behaviour of a number of PFAAs, alkanes, and perfluoroalkanes: the optimized OPLS-AA model based on ab initio calculations by Pádua [19]; and the exponential-6 force field based on the ab initio model for perfluoroalkanes developed by Borodin et al [20] The predicted surface tensions of PFAAs were sometimes lower than both the n-alkane and perfluoro-n-alkane with the same number of carbon atoms. Pierce et al [18] again found segregation of the fluorinated segments to the surface, with a normal orientation of the molecules relative to the interface. However, the simulated densities and surface tensions were essentially compared with experimental data for the n-alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive computational studies focusing on the interfacial properties of the PFAA molecules have been performed by Hariharan and Harris [17] and by Pierce et al [18]. A united-atom approach was used by Hariharan and Harris [17] to examine the surfaces of n-decane, perfluoro-n-decane, F 5 H 5 , and F 10 H 10 in terms of surface tension, density profiles and molecular orientations; their study indicated that in PFAA molecules the perfluorinated segments tend to segregate to the surface and are preferentially oriented perpendicularly to the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Hariharan and Harris 23 presented a UA-based study in which their model could not capture surface-tension differences between decane and perfluorodecane. References [24][25][26] to that work 23 seem to suggest that this is caused by an inherent limitation of the UA method. However, the results in this work demonstrate that this is not the case; rather, the issue is with the specific UA model used and its parameterization.…”
Section: Resultsmentioning
confidence: 99%